2009
DOI: 10.1243/09576509jpe741
|View full text |Cite
|
Sign up to set email alerts
|

Experimental performance of a compliant scroll expander for an organic Rankine cycle

Abstract: A small-scale scroll expander was developed and tested. The expander was based on a compliant scroll compressor having a displacement of ∼6.8 cm3. A test loop was also developed for determining expander performance parameters. The loop employed a compressor to pressurize the working fluid up to 2758 kPa and a heat exchanger to create the expander inlet conditions that would characterize an operating power cycle. The expander was tested with R134a as the working fluid. For power output measurements, a dynamomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 9 publications
(10 reference statements)
0
40
0
1
Order By: Relevance
“…The resulting avoidance of nonproductive parameter combinations conserves computation effort and accelerates the selection of optimal scroll geometries. From this data the desired volume expansion ratio R VP of the expander can be inferred from the working fluid properties, assuming 95% volumetric efficiency (reasonable for scrolls) [2,4,19] and using an imputed isentropic efficiency from, e.g., Refs. [3,4], which may be inclusive of downstream losses from a generator.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting avoidance of nonproductive parameter combinations conserves computation effort and accelerates the selection of optimal scroll geometries. From this data the desired volume expansion ratio R VP of the expander can be inferred from the working fluid properties, assuming 95% volumetric efficiency (reasonable for scrolls) [2,4,19] and using an imputed isentropic efficiency from, e.g., Refs. [3,4], which may be inclusive of downstream losses from a generator.…”
Section: Resultsmentioning
confidence: 99%
“…While several investigations of scroll expander models and validation experiments are described in the literature [2][3][4][5][6][7], discussion of the choice of the scroll geometry, the single feature upon which all other properties depend, is generally limited to the case of circle involutes in low volume ratio compressor applications [8,9]. In contrast, the present work explores the effect of varying the basic scroll geometry as a method for developing novel scroll machinery at the higher volume ratios needed for many ORC applications.…”
Section: Introductionmentioning
confidence: 99%
“…E "`B`r p,max´rp,0˘´t an pπ{2 ξq˘{`B`r p,max´rp,0˘´a rctan`B`r p,max´rp,0˘˘˘ ( 16) rp " r p´4 r p ; Nr ot " N rot´3 000 3000 ; p˚" p´10 10 (17) r p,0 " r p,0,n`a0 Nr ot (18) ϑ " ϑ n`a1 p˚`a 2 Nr ot (19) r p,max " r p,max,n`a3 p˚`a 4 Nr ot (20) y max " y max,n`a5 p˚`a 6 pNr ot´Nrot,n q…”
Section: Thermodynamic Model Of the Orc System Based On Sse Integrateunclassified
“…Expanders come in two types: dynamic (turbine) [8,9] and positive displacement (volumetric) [10] such as rotary vane [11][12][13][14], scroll [15][16][17][18][19], twin screw [20], single-screw [21][22][23][24][25][26][27] and reciprocating expanders [28]. In the medium-low power range, the displacement expander is a better choice than the turbo generator, because the former has a low flow rate, low rotational speed and a high pressure ratio [29].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [26] found a maximum expander isentropic efficiency of 77% and power output of 1kW from a scroll expander modified from a compliant scroll compressor using R134 as working fluid. More precisely, it is important to determine some operating parameters for achieving the system maximum energy efficiency; these parameters include pressure ratio, inlet condition and electrical load applied to ORC system.…”
Section: Introductionmentioning
confidence: 99%